Crusting effects on erosion processes under simulated rainfall on a tropical Alfisol - Bajracharya, R. M.; Lal, R. (Hydrological processes, 1998)
Sealing and crusting of soil surfaces have dramatic effects on water infiltration into and runoff from soils, thereby greatly influencing erosion processes. This study focused on the effect of the initial stage of crusting on inter‐rill erosion processes for a crust‐prone Alfisol sampled from south‐central India. Soil aggregates ranging from 2·4 to 8 mm collected from ploughed (PL) and naturally vegetated (NV) treatments were subjected to rainfall simulation under laboratory conditions. Runoff from PL soil aggregates was 2–2·5 times higher, while percolation was 20–100% lower, than for NV aggregates. Soil wash and splash losses were 0·5–3 times greater for PL than for NV soil. Runoff and inter‐rill erosion were significantly higher during the wet simulation run compared with the dry run. The results indicated that NV soil aggregates were more resistant to breakdown from raindrop impact and slaking, and subject to less rapid sealing, than PL soil. Total soil loss was influenced most by initial aggregate stability and the extent of seal development. Splash and wash losses of soil both increased as a result of surface sealing regardless of soil condition for short (30–60 min) rainfall durations. High drying rates resulted in the highest crust bulk densities. Increased crust strength for PL soil compared with NV soil reflected the greater susceptibility of cultivated soil to surface sealing and crusting. © 1998 John Wiley & Sons, Ltd.